Respuesta :

7x - 3 + 4x = 19

7x + 4x - 3 = 19

11x - 3 = 19            | + 3

11x - 3 + 3 = 19 + 3

11x = 22            | : 11

11x : 11 = 22 : 11

x = 2

Answer B.

Answer:

B) 2

Step-by-step explanation:

(7x2) - 3 + (4x2) =19

14 - 3 + 8 = 19

11 + 8 = 19

19 = 19

the ecuation is true because both members are equals

when you have an expression like this you have to remeber that there are priorities

, first you have to solve the multiplications and division, then you have to solve the sum and the subtraction.